Molecular cloning and characterization of recombinant parasite antigens for immunodiagnosis of onchocerciasis. - Chandrashekar, R (1991)
Immunological cross-reactivity among nematodes has hampered the development of specific serodiagnostic assays for onchocerciasis. In the present study, an Onchocerca volvulus adult worm complementary DNA expression library was differentially screened with human sera from patients infected with O. volvulus and with an omnibus anti-nematode serum pool comprised of sera from patients infected with Brugia malayi, Loa loa, Wuchereria bancrofti, Mansonella perstans, Strongyloides stercoralis, Ancylostoma duodenale, Ascaris lumbricoides, and Dracunculus medinensis. Seven Onchocerca-specific clones were identified and screened with individual onchocerciasis patient sera. Additional studies were performed to characterize the most immunoreactive clones, OC 3.6 and OC 9.3. OC 3.6 produced a 152-kD beta-galactosidase fusion protein that was recognized in dot-immunoblots by 54 of 55 sera from onchocerciasis patients (98%). The OC 3.6 DNA insert is 996 bp long with an open reading frame of 627 bp and a 369-bp untranslated 3' end. OC 3.6 is closely related to a previously reported clone (OV 33-3), but it differs from that clone at both the 5' and 3' ends. OC 9.3 contained a novel 565-bp insert and produced a 138-kD fusion protein that was recognized by 46 of 55 sera from onchocerciasis patients (83%). Additional studies are in progress to develop and evaluate immunodiagnostic tests for onchocerciasis based on measurement of antibodies to these promising recombinant antigens.